Instructional leadership and pedagogical competence influencing teacher commitment in Indonesian junior high schools - Sagita , Devy Eka Yanthi; Setiawati, Merika; Hadiyanto, Hadiyanto; Sulastri, Sulastri (Indonesian Research Journal in Education |IRJE|, 2026)
This study aims to examine the influence of instructional leadership and pedagogical competence on teacher commitment in public junior high schools in West Pasaman Regency. A quantitative associative causal design was employed, involving 72 teachers selected through proportional stratified random sampling from a population of 241 civil servant teachers. Data were collected using a validated Likert-scale questionnaire and analyzed using descriptive statistics and regression analysis. The results indicate that instructional leadership significantly influences teacher commitment by 52%, while pedagogical competence contributes 36.5%. Simultaneously, both variables explain 61.5% of the variance in teacher commitment. Overall, teacher commitment is categorized as high, while instructional leadership and pedagogical competence are in the good category. These findings highlight the importance of strengthening instructional leadership and enhancing pedagogical competence to improve teacher commitment.